Insect Pest Managment Services Provided by Bats - Holly K. Ober (EDIS)
WEC-245, a 4-page illustrated fact sheet by Holly K. Ober, uses a questions-and-answer format to provide information about this insect-eating animal’s role in reducing crop pests and mosquito populations in Florida, and what Floridians can do to attract bats to their property. Includes additional sources of information. Published by the UF Department of Wildlife Ecology and Conservation, August 2008.